The Soil Bacterium Methylococcus capsulatus Bath Interacts with Human Dendritic Cells to Modulate Immune Function - Indrelid, Stine; Kleiveland, Charlotte; Holst, René; Jacobsen, Morten; Lea, Tor (Frontiers in Microbiology, 2017)
The prevalence of inflammatory bowel disease (IBD) has increased in Western countries during the course of the twentieth century, and is evolving to be a global disease. Recently we showed that a bacterial meal of a non-commensal, non-pathogenic methanotrophic soil bacterium, Methylococcus capsulatus Bath prevents experimentally induced colitis in a murine model of IBD. The mechanism behind the effect has this far not been identified. Here, for the first time we show that M. capsulatus, a soil bacterium adheres specifically to human dendritic cells, influencing DC maturation, cytokine production and subsequent T cell activation, proliferation and differentiation. We characterize the immune modulatory properties of M. capsulatus and compare its immunological properties to those of another Gram-negative gammaproteobacterium, the commensal Escherichia coli K12, and the immune modulatory Gram-positive probiotic bacterium, Lactobacillus rhamnosus GG in vitro. M. capsulatus induces intermediate phenotypic and functional DC maturation. In a mixed lymphocyte reaction M. capsulatus-primed monocyte-derived dendritic cells (MoDCs) enhance T cell expression of CD25, the γ-chain of the high affinity IL-2 receptor, supports cell proliferation and induce a T cell cytokine profile different from both E.coli K12 and Lactobacillus rhamnosus GG. M. capsulatus Bath thus interacts specifically with MoDC, affecting MoDC maturation, cytokine profile and subsequent MoDC directed T cell polarization.